PENGUNGKAPAN ENVIRONMENTAL, SOCIAL DAN GOVERNANCE DALAM MENINGKATKAN NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Kartika, Fiki; Hudaya, Faza; Septianingsih, Cesilia Arum (Kajian Ekonomi dan Bisnis, 2024)
Economic development in Indonesia continues to increase, and demand has also responded well. Even though not many companies have made Environmental, Social, and Governance (ESG) disclosures, understanding regarding the investment community continues to increase. ESG can be used as a standard for companies to implement policies that align with environmental, social, and governance concepts. This research to determine the influence of ESG on company value which is moderated by dividend policy in companies listed on the Indonesia Stock Exchange. The sample for this research is companies listed on the IDX in 2017-2021 period. The analysis carried out was a hierarchical regression using SPSS 21 software. The study concluded that ESG was proven to be able to influence the value of companies listed on the IDX 2017-2021 period. Dividend policy has also been proven to be able to moderate the influence of ESG on the value of companies listed on the IDX for the 2017-2021 period.   Keywords: Environmental, social, governance,ESG, Company Value, Dividend Policy